ENGLISH VIDEO TUTORIAL UNTUK MENINGKATKAN KETERAMPILAN MEMASANG KAMPAS REM BAGI ANAK TUNAGRAHITA RINGAN: Abstract - Rabah Humam Ghazi; Amsyaruddin Amsyaruddin; Irdamurni Irdamurni (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
The research was distributed by problems are five children of mild mental retardation class VII that have not been able to read the beginning with good and right so as to influence the outcome of learning they get. This research used an Agency Said method to form pre-experimental or quasy experiment with a kind of one group pretest-postest design. The research results show, a generation of kids able mental retardation in reading the beginning when analyzed by saw the value the average , when pre-test the child with mental retardation only 44 %. Next on posttest a generation of kids able mental retardation up by 78 % . Then the data processed that more scientific using the Mann Whitney test, obtained Uhit = 2.5 and Utab = 2 to the n = 5 the first significant 95 % and α = 0.05 .